Il castello di carte. La transizione all'età adulta dei giovani Neet a Roma - Nerli Ballati, Enrico; Köhler, Jan (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
The paper focuses on the transition to adulthood of young people not in education, employment or training (NEETs). In the Italian context, unemployment, inactivity and problematic transitions to work are strongly related to delayed transition to adulthood and patterns of dependency on family. Our study aims to identify pathways to adulthood of NEETs from a biographical perspective. We carry out a software-based qualitative content analysis on 32 in-depth interviews, which have been conducted with NEETs between 25 and 34 years old in Rome and its surroundings as a part of a research project founded by Sapienza University of Rome. An empirically grounded typology of transition to adulthood based on position in the household, biographical sequence of life events and subjective aspirations for autonomy is constructed and six types are presented and characterized regarding dependency patterns, expectations for the future and subjective strategies to leave NEET-condition.